2016
DOI: 10.9767/bcrec.12.1.758.119-126
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Oligomerization of Isobutene over Acid Treated Kaolinite Clay Catalyst

Abstract: Natural Kaolin Clay was calcined and treated by sulfuric acid. The resulting solid acid catalyst was characterized by FTIR, TGA, and X-ray powder diffraction (XRD) and tested for isobutene oligomerization in a gas phase. The characterization results showed that the acid treated clay underwent chemical and structural transformations. After acid treatment, the Si/Al ratio was increased, and the crystalline raw clay became amorphous. The effects of various parameters such as reaction temperature, reaction time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…TGA profile of processed clay show weight loss due the removal of the physisorbed water (below 100 °C), loss of the strongly bonded water molecules existing in the first coordination sphere of the interlayer ions (100–500 °C) and the loss of structural hydroxyl groups (500–900 °C) [45] . TGA analysis of palladium intercalated catalyst revealed that catalysts with higher metal loadings (Pd 6 wt % and Pd 10 wt %), were stable up to 900 °C with slight initial weight reduction, which could be ascribed to loss of water molecules [46] . However, the significant weight loss was observed with less metal loading particularly for Pd 2 % and Pd 4 %, which indicates that catalyst with higher metal loadings are more thermally stable.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…TGA profile of processed clay show weight loss due the removal of the physisorbed water (below 100 °C), loss of the strongly bonded water molecules existing in the first coordination sphere of the interlayer ions (100–500 °C) and the loss of structural hydroxyl groups (500–900 °C) [45] . TGA analysis of palladium intercalated catalyst revealed that catalysts with higher metal loadings (Pd 6 wt % and Pd 10 wt %), were stable up to 900 °C with slight initial weight reduction, which could be ascribed to loss of water molecules [46] . However, the significant weight loss was observed with less metal loading particularly for Pd 2 % and Pd 4 %, which indicates that catalyst with higher metal loadings are more thermally stable.…”
Section: Resultsmentioning
confidence: 96%
“…[45] TGA analysis of palladium intercalated catalyst revealed that catalysts with higher metal loadings (Pd 6 wt % and Pd 10 wt %), were stable up to 900°C with slight initial weight reduction, which could be ascribed to loss of water molecules. [46] However, the significant weight loss was observed with less metal loading particularly for Pd 2 % and Pd 4 %, which indicates that catalyst with higher metal loadings are more thermally stable. The maximum weight loss (%) was observed in 4 wt % Pd/Clay probably owing to the weakening of bonds in the clay in this case.…”
Section: Resultsmentioning
confidence: 97%
“…Three small peaks at 789, 755 and 696 cm -1 correspond to Si-O-Al vibrations and to OH groups perpendicular to the surface [29]. Lastly, the bands at 538 cm -1 (Si-O-Al deformation), 469 cm -1 (Si-O bending), 429 cm -1 (Si-O-Si bending) are typical of kaolinite clay mineral [24,30].…”
Section: Microstructure Of the Synthesized Materialsmentioning
confidence: 91%
“…In Fig. 2a, the kaolin clay exhibits bands at 3697 cm -1 corresponding to valence vibrations of surface hydroxyl clusters (OH stretching) [24], and 3620 cm -1 corresponding to the vibrations of the internal hydroxyl cluster (OH stretch) [25,26]. The band located at 3454 cm -1 characterizes silanol group (Si-O-H).…”
Section: Microstructure Of the Synthesized Materialsmentioning
confidence: 99%
“…3. Upon investigating the IR spectrum of clay, some significant peaks that lie at the range 500-550 cm −1 are assigned for Si-O-Al and Si-O-Si [65,66]. Other important peaks appear in the range 3200-3300 cm −1 .…”
Section: Ir Characterization Of the Hydrogel Nanocompositesmentioning
confidence: 99%